Providing Legal Certainty to the Board of Directors Through the Implementation of Integrated Governance, Risk and Compliance (GRC) So That There Are Limits of Liability for Problems and Losses Occurring in BUMN - Eunike Petra Rebecca Pariela; Azis Budianto (PT. ALHAFI BERKAH INDONESIA, 2025)
This study discusses the implementation of integrated Governance, Risk, and Compliance (GRC) as a legal protection mechanism for BUMN Directors in dealing with problems and losses that occur. GRC combines three main elements corporate governance, risk management, and legal compliance that work synergistically to increase transparency, and accountability, and reduce uncertainty in decision making. Effective GRC implementation provides legal certainty for Directors, by proving that they have acted in good faith and accordance with applicable regulations. This study also identifies challenges in implementing GRC in BUMN, as well as the importance of the role of technology and changes in organizational culture in supporting the implementation of an effective GRC system.